1991
DOI: 10.1161/01.res.69.1.228
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of skin sympathetic nerve discharge by central command. Differential control of sympathetic outflow to skin and skeletal muscle during static exercise.

Abstract: Microneurographic measurements of muscle sympathetic nerve activity (SNA) have suggested that, during static exercise, central command is much less important than skeletal muscle afferents in causing sympathetic neural activation. The possibility remains, however, that the sympathetic discharge produced by central commandis targeted mainly to tissues other than skeletal muscle. To examine this possibility, we recorded SNA with microelectrodes placed selectively in skin, as well as in muscle, nerve fascicles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
136
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 39 publications
8
136
1
2
Order By: Relevance
“…7 Central command refers to a signal emanating from the rostral brain that projects to autonomic circuits in the brainstem and is part of the generalized activation of motor and sympathetic neurons at the onset of exercise. 7 Several of our observations support a role of central command in initiating the SSNA response to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Central command refers to a signal emanating from the rostral brain that projects to autonomic circuits in the brainstem and is part of the generalized activation of motor and sympathetic neurons at the onset of exercise. 7 Several of our observations support a role of central command in initiating the SSNA response to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…3 SSNA is less tightly linked to baroreflex control but responds to central neural stimuli and arousal. 7 Previous studies suggest that SSNA is increased by central command and by input from mechanoreceptors but not from metabolically sensitive skeletal muscle afferents. 7,8 In addition, whereas MSNA typically rises in a time-dependent fashion and after the onset of exercise, 9,10 it has been suggested that SSNA may increase immediately before the onset of muscle contraction.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…I have previously attributed high P v in high P v POTS to a defective venoarterial reflex 19 and a related increased flow to the lower extremities due to the effects of gravity and the failure of venoarterial reflex-mediated vasoconstriction when upright. 20,21 Current data still suggest abnormal vasoregulation. However, I demonstrated increased supine resting resistance during venous hypertension, which suggests that vasoconstriction does occur during venous hypertension.…”
Section: Steady-state Arterial Vasoconstriction Is Abnormal In Potsmentioning
confidence: 99%